Association of sleep duration and quality with depression Among University Students and Faculty - Alqurashi, Yousef; Al Qattan, Ali; Al Abbas, Hassan; Alghamdi, Majed; Alhamad, Abdullah; Al Dalooj, Hashem; Yar, Talay; Al Khathlan, Noor; Alqarni, Abdullah; Salem, Ayad (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Highly competitive and demanding environments in educational institutions led to reduced sleep time for both students and faculty globally. The primary objective of this study was to determine the duration and quality of sleep among students and faculty of Imam Abdulrahman Bin Faisal University (IAU). The secondary objective was to explore the relationship between depression and sleep duration and quality among students and faculty.Methods: The study was conducted during 2021 in Dammam, Saudi Arabia. An online survey was disseminated among the university students. The survey form included: demographic data, Patient Health Questionnaire (PHQ9), Pittsburg Sleep Quality Index (PSQI) and Epworth Sleepiness scale (ESS). The responses were analyzed using bivariate and multivariate analysis.Results: A total of 509 responses satisfying the inclusion criteria were included (323 student and 186 faculty). The average sleep duration for the entire cohort was 6.21 ± 1.32 hours, with 6.5% sleeping less than 5 hours per night. The mean PSQI score was 7.61 ± 3.09, with 73.1% falling in the poor sleep quality category (PSQI score >5). The mean PHQ9 score was 8.86 ± 6.20, with 63.9% falling in the  mild depression category. The mean ESS score was 6.59 ± 4.02, with 11% having a score >10 (corresponding to excessive daytime sleepiness).Conclusions: A significant proportion of surveyed students and faculty IAU suffer from sleep insufficiency, poor sleep quality, and mild degree of depression. Initiatives to tackle the issue of poor sleep quality and quantity among university students and faculty are required.